2021
DOI: 10.1029/2021gl094817
|View full text |Cite
|
Sign up to set email alerts
|

Active Boulder Falls in Terra Sirenum, Mars: Constraints on Timing and Causes

Abstract: The last decade has seen significant improvements in the identification and monitoring of active surface processes on Mars. Repeat observations have allowed the study of a wide range of features and processes. Many of these studies have concentrated on changes observed on the slopes of crater walls, particularly of gully (e.g., Dundas et al., 2015) and recurring slope lineae (RSL) features (e.g., McEwen et al., 2014). To date, none of these active features have been driven by endogenic processes, with environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…From our survey, we find rockfall triggered by wind, thermal cracking and seismic shaking are reasonable triggers for the recent falls causing BFE. Our observations suggest that the present day occurrence of boulder falls is wide spread, and that they are happening more frequently (Figures 4d and 4e) than previously reported (Dundas & Daubar, 2020; Grindrod et al., 2021).…”
Section: Bfe Formationsupporting
confidence: 59%
See 1 more Smart Citation
“…From our survey, we find rockfall triggered by wind, thermal cracking and seismic shaking are reasonable triggers for the recent falls causing BFE. Our observations suggest that the present day occurrence of boulder falls is wide spread, and that they are happening more frequently (Figures 4d and 4e) than previously reported (Dundas & Daubar, 2020; Grindrod et al., 2021).…”
Section: Bfe Formationsupporting
confidence: 59%
“…Repeat temporal imaging has shown that boulder falls are ongoing on Mars, as first observed by the Mars Global Surveyor—Mars Orbiter Camera (Malin & Edgett, 2001) images from the southern hemisphere and Valles Marineris (https://www.msss.com/mars_images/moc/2005/09/20/bouldertracks/). Subsequently, several studies have used repeat temporal imaging using HiRISE to identify and study recent boulder falls (Dundas & Daubar, 2020; Dundas et al., 2019; Grindrod et al., 2021). The boulder fall tracks are predominantly present on crater walls and floors, but can originate from any steeply sloping surface (Bickel et al., 2020; Kumar et al., 2019; Sinha et al., 2020; Van der Bogert & Plescia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of rock breakdown is rockfalls, which have been observed to occur in repeat imaging of Mars (Grindrod et al, 2021;Vijayan et al, 2021) (Figure 9b). Roll/bounce marks left in the regolith in the wake of boulders (Figure 9c) have shown rockfall to be a recently active process on the Moon (Arvidson et al, 1975;.…”
Section: Weatheringmentioning
confidence: 93%